APPLICATION OF ANTIFRICTION ALUMINIUM-SILICON ALLOY - V. Ju. Stetsenko; A. I. Rivkin (Литьë и металлургия)
It is shown that antifriction aluminium-silicon alloy is perspective material for change of the parts of heavy and expensive bronze in different frictional units of machines and mechanisms.